Inhibition of Ion Migration for Reliable Operation of Organolead Halide Perovskite‐Based Metal/Semiconductor/Metal Broadband Photodetectors. (21st March 2016) - Kwon, Ki Chang; Hong, Kootak; Van Le, Quyet; Lee, Sun Yong; Choi, Jaeho; Kim, Ki‐Bum; Kim, Soo Young; Jang, Ho Won
Abstract : Organolead halide perovskites (OHPs) have attracted extensive attention as light harvesting materials for solar cells recently, because of their high charge carrier mobility, high photoconversion efficiencies, low cost, and simple methodology. Despite these advantages, the OHPs exhibit sweep‐dependent hysteresis behavior in current–voltage characteristics films, deteriorating the reliability of devices based on the OHPs. This study demonstrates reliable high on/off ratio ( I on / I off = 10 4 ) CH3 NH3 PbI3 broadband photodetectors with buffer layer‐free simple metal/semiconductor/metal lateral structure. At high external bias, poor on/off ratios and spikes in dark current and photocurrent are observed due to the migration of charged defect ions. The ion migration can be effectively inhibited at low external bias, and thus the devices show high I on / I off ratios and spike‐free dark current and photocurrent. In addition, prevention of the prepoling in the CH3 NH3 PbI3 films by operating at the low external bias results in pronouncedly enhanced signal‐to‐noise ratios even under low intensity incident light. These results strongly propose that inhibiting the migration of charged defect ions in CH3 NH3 PbI3 films is a key in developing reliable high performance CH3 NH3 PbI3 ‐based devices. Abstract : A reliable and high performance perovskite‐based lateral‐structure photodetector is achieved by inhibition of charged defect ions migration at low external bias. The electrical history severely affects the device performance and the poling at high external bias should be avoided in order to obtain reliable performances from CH3 NH3 PbI3 photodetectors, especially for detecting low‐intensity light.